EVALUASI HASIL PELATIHAN DAN PENDIDIKAN UNTUK PENANGANAN PRA RUMAH SAKIT TERHADAP PENDERITA CEDERA - Soemarko, M. (Jurnal Kedokteran Brawijaya, 2004)
ABSTRACT The  purpose  of  organized  trauma  system  management  of  pre  hospital  care  of  seriously  injured  patients  is  to  ensure  the  early intervention and transfer savely the patients to the best equipped facility to care of their injuries. The aims this research is to evaluate the results and the effectiveness of the training and education of pre hospital management in Saiful Anwar Hospital.  The method this research are an observational study of injured traffic accident patients preHospital care in Saiful Anwar General Hospital Malang. Training and education have been done intensively and continuously after August 1999 until now. The comparation was between 1st April until 31st Juli 1999 and 1st April until 31st Juli 200. The result of this research, a significant progress in pre hospital treatment, ambulance transportation and communication between field attendance and the trauma center. But significantless of progression in pre hospital medical records. Only reveral system from health center was significant developed. The intensive training and education of pre hospital management to the injured patient had a significant good results. The training and education must be continued and developed for a better results in the future.  Key words : Injured patients, pre hospital care, training and education.